2015
DOI: 10.1128/iai.02474-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Plasmodium falciparum Properties of the Full Set of Human Secreted Phospholipases A 2

Abstract: We have previously shown that secreted phospholipases A 2 (sPLA 2 s) from animal venoms inhibit the in vitro development of Plasmodium falciparum, the agent of malaria. In addition, the inflammatory-type human group IIA (hGIIA) sPLA 2 circulates at high levels in the serum of malaria patients. However, the role of the different human sPLA 2 s in host defense against P. falciparum has not been investigated. We show here that 4 out of 10 human sPLA 2 s, namely, hGX, hGIIF, hGIII, and hGV, exhibit potent in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…PLA2G2F selectively hydrolyzes DHA-containing plasmalogen-PE (P-PE) in skin-extracted phospholipids to yield DHA and plasmalogen-lysophosphatidylethanolamine (P-LPE) at a physiological concentration . PLA2G2F also hydrolyzes lipoprotein phospholipids to release PUFAs in vitro, which in turn prevent the in vitro growth of the malaria parasite (Plasmodium falciparum) in infected erythrocytes (Guillaume et al, 2015). However, the lipoproteinhydrolytic and antimalaria actions of PLA2G2F need to be confirmed in vivo.…”
Section: Group Iif Spla 2 (Pla2g2f)mentioning
confidence: 99%
See 1 more Smart Citation
“…PLA2G2F selectively hydrolyzes DHA-containing plasmalogen-PE (P-PE) in skin-extracted phospholipids to yield DHA and plasmalogen-lysophosphatidylethanolamine (P-LPE) at a physiological concentration . PLA2G2F also hydrolyzes lipoprotein phospholipids to release PUFAs in vitro, which in turn prevent the in vitro growth of the malaria parasite (Plasmodium falciparum) in infected erythrocytes (Guillaume et al, 2015). However, the lipoproteinhydrolytic and antimalaria actions of PLA2G2F need to be confirmed in vivo.…”
Section: Group Iif Spla 2 (Pla2g2f)mentioning
confidence: 99%
“…With regard to polar head groups, PLA2G2A and other group II sPLA 2 s show preference for phosphatidylethanolamine (PE) over phosphatidylcholine (PC), while PLA2G10 is very active on PC, and these preferences can be partly explained in terms of crystal structure (Pan et al, 2002;Scott et al, 1991). With regard to sn-2 fatty acids, PLA2G1B, PLA2G2A, and PLA2G2E do not distinguish fatty acid species, PLA2G5 prefers fatty acids with a lower degree of unsaturation (eg, oleic acid (OA)), and PLA2G2D, PLA2G2F, PLA2G3, and PLA2G10 show preference for polyunsaturated fatty acids (PUFAs) such as arachidonic acid (AA) and docosahexaenoic acid (DHA) to various degrees (Chen & Dennis, 1998;Chen, Engle, Seilhamer, & Tischfield, 1994b;Cupillard, Koumanov, Mattei, Lazdunski, & Lambeau, 1997;Guillaume et al, 2015;Hanasaki et al, 1999;Miki et al, 2013;Mitsuishi, Masuda, Kudo, & Murakami, 2007;Murakami et al, 2003;Murase et al, 2016;Pruzanski et al, 2005;Sato et al, 2014;Yamamoto et al, 2015). Although the substrate specificity of sPLA 2 s differs according to the in vitro assay conditions employed, particularly when excess amounts of the enzymes are used, the overall tendency is recapitulated in several if not all in vivo systems, often with even more selective patterns of hydrolysis that may be affected by the phospholipid compositions of the target membranes.…”
mentioning
confidence: 99%
“…The anti-malaria property of sPLA 2 s is dependent on their ability to release PUFAs relative to other fatty acids from lipoproteins, sPLA 2 -IIF being the most PUFA-selective sPLA 2 . Indeed, lipoprotein phospholipids are potently hydrolyzed, with marked PUFA preference, when treated with sPLA 2 -IIF in vitro [87,88] or in Pla2g2f-TG mice in vivo (Fig. 3C).…”
Section: Other Potential Functionsmentioning
confidence: 98%
“…Recombinant sPLA 2 -IIF has a potent capacity to prevent malaria infection in vitro [87]. The anti-malaria property of sPLA 2 s is dependent on their ability to release PUFAs relative to other fatty acids from lipoproteins, sPLA 2 -IIF being the most PUFA-selective sPLA 2 .…”
Section: Other Potential Functionsmentioning
confidence: 99%
“…Both endogenous and exogenous sPLA 2 s play direct and indirect roles in host defence against various types of bacteria, parasites and viruses [ [17] , [18] , [19] , [20] , [21] ]. For example, an early study showed that several snake and bee venom sPLA 2 s exhibit direct antiviral activity by blocking HIV-1 virus entry into host cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%